(untitled) (Journal of Pharma Insights and Research, 2025)
Hepatic diseases, ranging from viral hepatitis and liver fibrosis to hepatocellular carcinoma (HCC), constitute a formidable global health challenge that requires the development of advanced therapeutic interventions. Conventional pharmacotherapies are frequently impeded by non-specific biodistribution, resulting in suboptimal drug concentrations at the target site and debilitating systemic toxicity. In response to these clinical deficits, nanomedicine has emerged as a pivotal frontier, with Solid Lipid Nanoparticles (SLNs) gaining prominence due to their superior biocompatibility, physical stability, and controlled release profiles. A promising strategy to augment the therapeutic index of anti-hepatotoxic agents involves the surface engineering of SLNs with galactose moieties to strategically exploit the Asialoglycoprotein Receptor (ASGPR). This receptor, abundantly and exclusively expressed on the sinusoidal surface of mammalian hepatocytes, serves as a high-affinity portal for receptor-mediated endocytosis. Galactose-modified SLNs facilitate the active internalization of therapeutic payloads directly into the hepatic parenchyma by mimicking natural desialylated glycoproteins, thereby bypassing non-target organs. This review focusses on the mechanistic rationale behind ASGPR targeting, elucidating the structural advantages of lipid-based nanocarriers in preserving drug stability and enhancing cellular uptake. The review also highlights the potential of this "lock-and-key" approach to revolutionize the management of chronic liver diseases by enabling precise dosage reduction and minimizing off-target adverse effects. The combination of ligand-anchored lipid nanotechnology signifies a paradigm shift towards precision medicine, offering a robust platform for the delivery of both small molecules and complex nucleic acid therapeutics